Radionuclide migration in fresh water from nuclear power plant liquid effluent discharged: (Hypothetical case study). Issue 2 (April 2020) - Ayoub, Anuor AT; Song, Yushou; Sagiroun, Mamoun IA; Omhahmed,
Abstract: Radionuclide migration in ecosystems including rivers is one of the major radioecology problems. Aquatic ecosystems can contribute to radionuclide migration at very long distances from intake or forming sources. This study provides new insights into field of radiological by studying the behavior of radionuclide transported in river, resulting of discharged effluent radionuclide from nuclear power plants (NPPs) during normal operation in the river, as hypothetical case study. It was demonstrated that, the concentration of radioactivity in the river at the same side of the NPPs, it's a higher than opposite side of river bank. In addition, we show that, the maximum concentration found at the point of discharged and clearly decreased with distance. In order to assessment of radiological hazard of ionizing radiation to non-human biota, ERICA toll software Tier 2 were used to calculate the Total Dose Rate per organism, the maximum value was found to the Insect larvae [2.094 µGy h -1 ], this value was below the screening dose rate 10 μGy h −1 .